Rancang bangun website toko online dengan penerapan product knowledge dan strategi up selling pada Mc store surabaya - Priyantina, Reza Amalia; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: MC Store is a Cosmetic Shop that sell the various types of cosmetic since 2008. MC Store Company increased from 85 (Eighty Five) product become 320 (Three Hundred Twenty) product. In the selling system now, Have a weakness as a costumer have difficulty in search the product and hard to find the information product and less attention metrosexual behavior because metrosexual people sometimes to be shy if come to the real store. MC Store also difficult for searching product report many buyers, report stock and turnover sales report.To solve the problem, I make selling system have features information providers product explanation (Product Explanation), recommendation up selling, searching product features, Purchase and Payment, Make a report sort good stuff, Daily stock, Selling transaction and Selling profit.From the evaluation system, The system can showing the information product explanation and the cover all attribute explanation product, Explanation the benefit of product and give the recommendation of value for the consumer, Give the explanation product have expensive price from the other (Up Selling), Provide the features searching, Purchase and Payment, Give goods selling reports, Product stock, Selling transaction and Selling profit.